A Model for Islamic Community Development Based on Local Commodities: An Analysis of the TRENDI Movement in Enhancing the Self-Reliance of Sugarcane Farmers - Mahlil Bunaiya; Zelfeni Wimra (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2026)
This study examines the model of Islamic community development based on local commodities through the TRENDI (Tebu Aren Indonesia) movement in Nagari Bukik Batabuah, Agam Regency. The research employs a qualitative inquiry and research design with a case study approach conducted over three months (January–March 2026). Data were collected through in-depth interviews, observation, and documentation involving community producers, traditional actors, innovators, and institutional leaders. The findings reveal that the main challenges faced by sugarcane farmers are structural dependency on middlemen, limited innovation, and low economic literacy, which hinder value creation. The TRENDI movement addresses these issues through an integrated approach combining traditional values, empowerment, and literacy, leading to increased capacity, product innovation, and improved bargaining position. This study formulates a model of Islamic community development based on three pillars: strengthening communal values, innovation-based economic empowerment, and capacity building. The study concludes that sustainable economic independence can be achieved through the integration of social values, knowledge, and innovation within a community-based framework.